Treating Students as Customers in Higher Education Institutions and its Impact on their Academic Performance - Safdar, Bilal; Habib, Aqib; Amjad, Ahsan; Abbas, Jawad (International Journal of Academic Research in Progressive Education and Development, 2020)
Students are considered as the main source of income for almost all higher education institutions (HEIs). For this reason, HEIs have started treating them as their customer and trying to ensure their satisfaction at all levels. The current research aims to investigate what is the impact of treating students like customers in HEIs on their academic performance. The challenges are examined in this research by taking quantitative responses from 153 undergraduate students studying at different universities located in Islamabad, Pakistan using five points Likert scale. The questionnaire was focused on customer orientation which is also taken as mediating variable in the current study, behaviour related to grade goal, learner identity, and academic performance. The empirical analyses show that students as customer approach negatively impact on their academic performance. Moreover, customer orientation partially mediates the relationship between learner identity, grade goal, and students’ academic performance. This research also provides guidelines for the management of HEIs to counter this issue and proposes strategies for improvements in students’ academic performance.